DIPLOMASI PERTAHANAN INDONESIA MELALUI NAVAL DIPLOMACY DAN SEA POWER DI LAUT CINA SELATAN PADA TAHUN 2020 - Lutfi Kurniawan (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
The implementation of defense diplomacy specifically in the maritime area is still a problem that lies on diplomacy process within one state. There is still a too-wide understanding of defense diplomacy defense strategy itself in state’s maritime area, especially in the maritime diplomacy. Thus, the implementation of defense diplomacy within maritime area of the state is still inadequate and ineffective. Previous studies show that maritime diplomacy is a strategy within defense diplomacy that is not specific, too wide; involving the only usage of military actors; meanwhile naval diplomacy is one of the defense diplomacy concepts that also involves non-military actors. In completing previous studies, the researcher argues that naval diplomacy is a defense diplomacy concept that is way more effective to be implemented in the maritime area of one state compared to maritime diplomacy. The naval diplomacy is also can be more effective if it is applied in Indonesia’s defense diplomacy. This study specifically pictures the Indonesia’s defense diplomacy strategy within its maritime area that intersects with the South China Sea (SCS) area in which naval diplomacy strategy is used according to Ken Booth. This study uses qualitative method, data are gathered through secondary data including news and previous studies about defense diplomacy. Result of this study is the naval diplomacy and sea power, as one of defense diplomacy concept, is an effective strategy to be applied in Indonesia’s maritime area that intersects with SCS since naval diplomacy also involves negotiation process with the non-state actors. Unfortunately, this strategy is still not effective yet to be implemented in Indonesia back in 2020.